Modern anatomical locking plates are associated with increased postoperative wound complications and unplanned surgical revisions compared to standard tubular plates in the management of unstable ankle fractures: a comparative cohort study in 595 patients - Patrick Gahr; Manuel Matthis; Lennart Schleese; Dagmar-C. Fischer; Thomas Mittlmeier (Patient Safety in Surgery)
Abstract Background The clinical benefit of locking plates in distal fibula fractures has not yet been proven. In addition, the risk of wound complications appears to be higher than with conventional tubular plates. We hypothesize that the benefits of locking plates in terms of biomechanical properties are outweighed by a higher risk of wound complications. Methods We conducted a retrospective review of fibula fractures treated by osteosynthesis with either a conventional one-third tubular plate or an anatomically shaped locking plate from January 1, 2015 to December 31, 2021. We recorded baseline data and relevant comorbidities and defined the need for revision surgery due to wound-related or mechanical complications as primary endpoints. Results A total of 595 out of 727 patients were eligible for our study. Of these 595 fractures, 526 were fixed with a one-third tubular plate, 69 with a locking plate. Revision surgery was required in 54 patients, in 51 cases due to wound complications. Three patients required revision surgery for mechanical reasons and all of them were younger than 40 years of age, have not been diagnosed with osteoporosis, but experienced complex fracture types. As the third tubular plate and locking plate groups differed in terms of age and comorbidities, we performed a 2:1 matching based on age and gender, leaving data from 138 patients receiving a third tubular plate. While the two groups were comparable in many aspects, the rate of wound complications was significantly higher in the locking plate group. Although the locking plate group had a higher percentage of diabetes mellitus, there was no correlation between this comorbidity and the higher revision rate in this group. Conclusions Our data do not support the general use of locking plates in the treatment of distal fibular fractures. The risk of mechanical complications in osteoporotic ankle fractures seems to be overrated, as there were no mechanical revisions in the osteoporotic subgroup. The rate of wound-related revision surgery was significantly higher after the use of locking plates. This might be attributed to the greater thickness of locking plates.